The Relation between the Transformational Leadership Behavior and Spiritual Intelligence Behavior of School Administrators under Nakhon Ratchasima Primary Educational Service Area Office 7 - Rachchapongchayanon, Nannapas; Thanaseelangkun, Chaturong (Ratchaphruek Journal, 2014)
This research aimed 1) to study the transformational leadership of school administrators in the schools under Nakhon Ratchasima Primary Education Service Area Office 7 and the spiritual intelligence behavior of the school administrators and 2) to find the relationship between the transformational leadership behaviors and spiritual intelligence behavior of the school administrators. The 144 samples of the study were the school administrators out of 228 population under Nakhon Ratchasima Primary Education Service Area Office 7 using the Krejcie & Morgan Table. The simple random was used to stratified random sampling. The research instrument used for data collecting was the questionnaire in a check-list and a 5 rating-scale form. Mean, standard deviation and Pearson’s Coefficient Correlation were employed as statistical analyses. The findings were as follows : 1. The Transformational leadership behavior of school administrators in Nakhon Ratchasima Primary Education Service Area Office 7 was overall at the highest level. ( = 4.53, S.D. = .36) 2. The Spiritual intelligence behavior of school administrators in Nakhon Ratchasima Primary Education Service Area Office 7 was overall at the highest level. ( = 4.57, S.D. = .37) 3. The analysis of relationship between the transformational leadership and the spiritual intelligence behaviors of the school administrators. Using Pearson’s Coefficent Correlation was positively highest (r = .641**) with statistical difference at .01 level of significance.